A short, rigid linker between pyrene and guanidiniocarbonyl-pyrrole induced a new set of spectroscopic responses to the ds-DNA secondary structure. Issue 6 (11th December 2014) - Radić Stojković, Marijana; Piotrowski, Patryciusz; Schmuck, Carsten; Piantanida, Ivo
Abstract : A DNA-targeting dye exhibited pH-dependent selectivity toward AT-DNA (pH 7) or GC-DNA (pH 5), accompanied by fluorimetric (pH 5) and ICD (pH 7) recognition. Abstract : A novel pyrene-guanidiniocarbonyl-pyrrole dye, characterised by a short, rigid linker between the two chromophores, interacts strongly with ds-DNA but only negligibly with ds-RNA. Under neutral conditions the dye shows strong selectivity toward AT-DNA (with respect to GC-DNA). Binding is accompanied by a specific ICD band at 350 nm and fluorescence quenching for all DNAs/RNAs studied. At pH 5 the affinity of the dye is reversed, now favouring GC-DNA over AT-DNA. A strong emission increase for AT-DNA is observed but with quenching for GC-DNA.